Testing, simulation and soft-optimization of R410A low-GWP alternatives in heat pump system. (December 2015) - Alabdulkarem, Abdullah; Eldeeb, Radia; Hwang, Yunho; Aute, Vikrant; Radermacher, Reinhard
Highlights: Drop-in tests of three R410A low-GWP alternative refrigerants were performed. The results show that R32 and L41a are good replacement candidates for R410A. Most of the predicted COP and capacity results of R32 experiments agree with the measured values. Varying the compressor size and adding a suction line heat exchanger to the system were investigated. Abstract: The environmental impact of high global warming potential (GWP) refrigerants pushed the HVAC&R industry to investigate alternative refrigerants. R410A is a common refrigerant for air conditioning and heat pumping applications, but has a GWP of 2088. Drop-in tests of three R410A low-GWP alternative refrigerants (R32, D2Y60 and L41a) in a 10.55 kW capacity split heat pump unit were performed. The results show that R32 and L41a are good replacement candidates for R410A. A finite volume heat exchanger model and component based vapor compression system simulation tools were validated against the experimental data. Most of the predicted COP and capacity results of R32 experiments lie within 5% of the measured values, which is in good agreement with the experiments. Further investigation was carried out by varying the size of the compressor and adding a suction line heat exchanger to the system to match the capacity to that of R410A.